Pengaruh Metode Mencongak terhadap Hasil Belajar Matematika - Abdul Karim (JKPM (Jurnal Kajian Pendidikan Matematika), 2017)
The purpose of this research is to determine the impacts of looked up method on learning achievement in multiplication and division on the students grade IV at SDN Mekar Jaya 10 central Depok II. The method is used to analyze is experiment method. Meanwhile, hypothesis test used t test for the average difference which examined normality by using liliefors test and homogeneity test by barlet test. Based on requirements of data analysis by using liliefors formula X2 test ? X2 table, the data is in normally distribution, meanwhile for homogeneity X2  test ? X2 table, the data’s varians is homogen. Based on hypothesis test for the average difference by  t test at significance level 0.05 for DK 58 is 2.0021 and the result is 3.752, so Ho is rejected and H1 is received and hypothesis is received. Based on the result of the analysis, it can be concluded that there are impacts of looked up method on learning achievement in multiplication and division on the students grade IV at SDN Mekar Jaya 10 central Depok II.